16-2t=t+94t

Simple and best practice solution for 16-2t=t+94t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-2t=t+94t equation:



16-2t=t+94t
We move all terms to the left:
16-2t-(t+94t)=0
We add all the numbers together, and all the variables
-2t-(+95t)+16=0
We get rid of parentheses
-2t-95t+16=0
We add all the numbers together, and all the variables
-97t+16=0
We move all terms containing t to the left, all other terms to the right
-97t=-16
t=-16/-97
t=16/97

See similar equations:

| 16x+0.25(12-x)=0.43(-12) | | x-(-0.07)=4.5 | | n+1/n^2+2n-3=n/n+3-1/n-1 | | 3y=36-6y | | t+1/2t-1=5/7 | | 35x+25=140x+175 | | 5y+3=5(4)-2(1) | | y/5+8=24 | | 12x-4=3x-2+6x | | 20x+60=40x+80 | | 100+x/5=-10x+-10x-1 | | -19+12x-10x=-18 | | 7.1x-4.7=62.3 | | (3x+8)^2=64 | | 28–x=3x | | .9(90)=20+16p | | 6x+1/2x+(-1/2)=-(1/2) | | 20+16p=81 | | 12x-34=8x+15 | | -5=n/3 | | (3x+8)2^=64 | | 2x+9+3x+3x=3x+1 | | 2x+9+3x+3x=2x+8 | | 2x+9+3x+3x=2x+7 | | 2x+9+3x+3x=2x+6 | | 2x+9+3x+3x=2x+5 | | 2x+9+3x+3x=2x+4 | | 2x+9+3x+3x=2x+3 | | 2x+9+3x+3x=2x+2 | | 2x+9+3x+3x=2x+1 | | 2x+9+3x+3x=1x+9 | | 2x+9+3x+3x=1x+8 |

Equations solver categories